The Relationship between Physical Activity and the Incidence of Diabetic Peripheral Neuropathy in Type II Diabetes Mellitus Patients at Maesan Public Health Center - Aditiya Nurul Hamdi, Mochammad; Sasmiyanto; Sasmito Adi, Ginanjar (Universitas Bondowoso, 2024)
Introduction: Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose (blood sugar) levels exceeding normal. a complication of Type II DM is diabetic neuropathy. Diabetic neuropathy is damage caused by high blood sugar that injures nerves throughout the body. Management of diabetic neuropathy includes blood sugar control, pain treatment, and regular physical activity. Physical activity plays a role in reducing insulin resistance through various mechanisms. The purpose of this study was to determine the relationship between physical activity and the severity of diabetic peripheral neuropathy in type II DM patients at Maesan Health Center. Method: This research design uses a correlation with a crosssectional approach, the sample size is 65 patients with type II diabetic peripheral neuropathy who are at the Maesan Health Center which is taken using consecutive sampling technique. The analysis used in this study was spearman rho with α = 0.05. Result: The results of this study were 28 respondents with high physical activity with the severity of diabetic peripheral neuropathy in the asymptomatic category and symptomatic severity of 7 respondents Conclusion: The statistical test results obtained p value (0.000) so that H1 is accepted, which means that there is a significant relationship between physical activity and the severity of diabetic peripheral neuropathy in type II diabetes. The value of the correlation coefficient obtained a correlation coefficient of (-0.713) which means including a very strong relationship, with the relationship between the two variables being negative